Building multimode quantum optical networks - Walmsley, I; Nunn, J; Langford, N; Datta, A; Zhang, L; Smith, B; Thomas-Peter, N; Spring, J; Metcalf, B; Englland, D; Reim, K; Michelberger, P; et al. (2011)
Light offers a route to the generation of macroscopic quantum states based on both multiple photons (e.g. Schrödinger kittens) and multiple modes (e.g. Dicke-Werner). The combination of these approaches affords new possibilities in both fundamental physics and in technological applications. The routes to building scalabl networks embodying such systems from feasible laboratory resources will be discussed. © 2011 OSA.